The impact of mandatory conflict of interest disclosures on editors' manuscript acceptance decisions: A cross‐sectional observational study. Issue 2 (26th March 2022) - Berdahl, Carl T.; Addo, Newton; Callaham, Michael L.
Abstract: Objective: Although current ethical standards mandate conflict of interest (COI) disclosure by authors of peer‐reviewed publications, it is unknown whether disclosure affects a manuscript's fate. Our objective was to identify associations between author COI disclosure and editorial decision to publish. Methods: We performed a cross‐sectional observational study of editorial decisions for original research and brief research report manuscripts submitted to Annals of Emergency Medicine between June 2014 and January 2018 using data from the journal's editorial decision software and data from a prior study that characterized author COI for the same manuscripts. Outcomes of interest included final editor decision to publish (primary), initial editor decision, and number of revisions. We compared outcomes for manuscripts with COI versus those without and by type of COI (commercial/government/other). Results: Out of 1312 manuscripts in the sample, 65.1% had no COI declarations, and 34.9% had one or more. Overall likelihood of editorial decision to publish was 13.5% (115/854) for articles without COI and 26.9% (123/458) for those with COI. Overall likelihood of editorial decision to publish was 19.8% (19/96) for articles with commercial COI only versus 33.3% (35/105) for those with government COI only. Conclusions: Articles with author‐reported COI were more likely to be published than those without such a declaration. Additionally, results suggest that reports of government COI are associated with improved chance of publication. Authorities should consider relaxing COI requirements temporarily to allow investigators to perform larger scale, randomized controlled studies of the impact of mandated COI disclosure.